The Implementation of Green Logistics in Road Transportation - Aldona Jarašūnienė; Darius Bazaras (The Baltic Journal of Road and Bridge Engineering)
The article presents an analysis of academic literature in an attempt to identify the importance of the implementation of green logistics in road transportation. Areas of concern as well as solution and implementation opportunities are presented. A research of transportation companies was conducted in an attempt to understand the real situation regarding the implementation of green logistics measures. The research results are presented in the article. Solutions are provided in the form of a conceptual model for the implementation of green logistics measures in transportation organisations. Nowadays the interest in ecology, minimization of fossil fuel usage, and mitigation of harmful road transportation consequences is rapidly increasing. Eco-friendly vehicles, effective transportation system, application of advanced technologies and innovations should become the main factors in promoting the implementation of green logistics in the transportation sector to mitigate negative effects on the environment. In order to maintain their competitive advantage and customer satisfaction, transportation organisations should begin implementing the concept of green logistics in their businesses. The significance of the concept of green logistics can be observed on global, regional, and national levels. Business is still seen as the leader, responsible for initiation and implementation of ecological logistics principles. The implementation of green logistics is critically important; however, lack of funding and collaboration between the public and the private sectors prevent companies from adopting green logistics measures. Economic driving classes, employee education, electric and hybrid cargo-handling vehicles are some of the possible green logistics measures.